2006
DOI: 10.5860/crl.67.4.354
|View full text |Cite
|
Sign up to set email alerts
|

Print versus Electronic Journal Use in Three Sci/Tech Disciplines: The Cultural Shift in Process

Abstract: This study examines journal use in three scientific disciplines. A previous study found that print use increased after electronic access was added. This article uses the same methods to determine if the increase in the use of the paper has continued. A cultural shift has happened between the two studies. Although the use of paper journals increased with the advent of e-journals, a shift in use patterns has occurred and patrons now favor electronic format. There are disciplinary differences in the use of paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 6 publications
0
13
1
Order By: Relevance
“…Electronic journals (e-journals) have achieved widespread and enthusiastic acceptance within the scientific disciplines of the higher education community, and are now an integral part of academic science library collections. 1 Much of the optimism for the success of electronic books (e-books) seems to stem from linked assumptions that the convenience, usability, and approbation of e-journals will be paralleled in e-books. E-book collections are thus being developed in response to expectations for point-of-need accessibility in the same way that e-journals have.…”
Section: Introductionmentioning
confidence: 99%
“…Electronic journals (e-journals) have achieved widespread and enthusiastic acceptance within the scientific disciplines of the higher education community, and are now an integral part of academic science library collections. 1 Much of the optimism for the success of electronic books (e-books) seems to stem from linked assumptions that the convenience, usability, and approbation of e-journals will be paralleled in e-books. E-book collections are thus being developed in response to expectations for point-of-need accessibility in the same way that e-journals have.…”
Section: Introductionmentioning
confidence: 99%
“…Use data for 2003 shows that print use declined to 23 percent. However, the second WSU study conducted by Brady et al 20 of Chemistry, MME, and Physics showed more dramatic drops in print use by 2003, with Chemistry at 5 percent, MME at 13 percent, and Physics at 4 percent. Use of the geology print collection did not decline as dramatically over the same period.…”
Section: Discussionmentioning
confidence: 99%
“…A representative study is Brady, McCord, and Galbraith's analysis of the 2003 print and e-serial use of researchers at Washington State University's Owen Science and Engineering Library. 5 Comparing the results of their analysis with a previous study conducted at the same site, the authors discovered that use of the library's serial collection in electronic formats increased from 71 percent of total use in 2001 to 94 percent of total use in 2003. The authors believe their findings show a "cultural shift" in user preferences.…”
Section: Use Studiesmentioning
confidence: 97%